2006
DOI: 10.1021/bi060511j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of HCV Polymerase Inhibitors at Individual Steps of the Polymerization Reaction

Abstract: Little is known about the mechanism of HCV polymerase-catalyzed nucleotide incorporation and the individual steps employed by this enzyme during a catalytic cycle. In this paper, we applied various biochemical tools and examined the mechanism of polymerase catalysis. We found that formation of a productive RNA-enzyme complex is the slowest step followed by RNA dissociation and initiation of primer strand synthesis. Various groups have reported several classes of small molecule inhibitors of hepatitis C virus N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 41 publications
5
33
1
Order By: Relevance
“…We tested RNAs derived from both isolates to exclude subtle differences in binding affinity due to potential isolate-specific cis-acting signals. Titration with increasing concentrations of RNA revealed a stoichiometry of only about 0.05 for the protein-RNA complex (data not shown), which compares to previously reported low values (20% [25]). The possibility of multiple NS5B molecules on the biosensor surface binding to the same RNA strand might account for the lower binding capacity determined here.…”
Section: Resultscontrasting
confidence: 61%
“…We tested RNAs derived from both isolates to exclude subtle differences in binding affinity due to potential isolate-specific cis-acting signals. Titration with increasing concentrations of RNA revealed a stoichiometry of only about 0.05 for the protein-RNA complex (data not shown), which compares to previously reported low values (20% [25]). The possibility of multiple NS5B molecules on the biosensor surface binding to the same RNA strand might account for the lower binding capacity determined here.…”
Section: Resultscontrasting
confidence: 61%
“…It has previously been suggested that finger-loop inhibitors form either unproductive complexes or interfere with the conformational changes required to adopt a more open conformation (11)(12)(13)(14). Our data show that a prototype compound of this class reduces the shift in average FRET values (reduced binding) and FRET fluctuations (reduced sliding-wrapping dynamics) in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 50%
“…Thumb pocket 1 non-nucleoside inhibitors (NNIs) or finger loop NNIs bind to a region of the thumb that is otherwise occupied by the flexible ⌬1 finger loop, which seems to impede productive RNA binding (Fig. 1b) (11)(12)(13)(14).…”
Section: The Hepatitis C Virus (Hcv)mentioning
confidence: 99%
See 1 more Smart Citation
“…Noncompetitive inhibition of NS5B polymerase activity with respect to NTPs has been reported (2, 15, 16). Based on co-crystallization studies with NS5B, it has been proposed that allosteric inhibitors may lock the NS5B protein in an inactive formation by binding tightly to the protein (16,17). It is important to understand how the binding affinity relates to inhibition potency and resistance to HCV inhibition.…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%